“Legalizing” the Great Bear Rainforest Agreements: Colonial Adaptations Toward Reconciliation and Conservation - Curran, Deborah (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2017)
The Great Bear Rainforest (GBR) agreements are heralded as one of the most important conservation initiatives in the world. They are intended to result in the protection of eighty-five per cent of the coastal temperate rainforest landscape on the British Columbia coast and to see seventy percent of the rainforest returned to old-growth forest. A clear terrestrial environmental success, the negotiation process and agreements are equally important for their enlivenment of Aboriginal rights and the governance authority of the Indigenous communities of the central and north coasts within a colonial law context. After stakeholders wrangled largely over the details of ecosystem-based management, First Nations and the provincial government engaged in government-to-government negotiations that are yielding agreement on the exercise of Aboriginal rights across an intact landscape, funding and priority access for First Nations’ ventures as part of a conservation economy, and enhanced roles in decision making. In the absence of treaties and in a common law Aboriginal rights and title context, these agreements are a robust example of the movement toward reconciliation. The purpose of this article is to describe how the protection of the GBR and the expression of Aboriginal rights in that process has manifested in colonial law, and to examine these agreements in the context of reconciliation in Canada. While unique and ongoing, as all reconciliation efforts will be, the GBR agreements locate land-based protection and governance at their core. As an applied, ongoing initiative, these agreements give life to the concepts of joint decision making and underscore the nation- and place-specific context of any reconciliation process that must adapt over time.